Ribosomal proteins mediate non-canonical regulation of gut inflammatory signature by crop contaminant deoxynivalenol - Juil Kim; BoGyoung Song; Ki-Hyung Kim; Yuseok Moon (Ecotoxicology and Environmental Safety)
Deoxynivalenol (DON), a prevalent mycotoxin produced by Fusarium species, contaminates global agricultural products and poses significant health risks, particularly to the gastrointestinal (GI) system. DON exposure disrupts ribosomal function, inducing stress responses linked to various inflammatory diseases, including inflammatory bowel disease (IBD). In this study, we elucidate a novel regulatory mechanism involving ribosomal proteins (RPs) RPL13A and RPS3, which mediate proinflammatory chemokine production in DON-exposed gut epithelial cells. Through a combination of transcriptomic analysis and experimental models, we demonstrate that while RPL13A negatively regulates inflammation by enhancing the anti-inflammatory transcription factor ATF3, RPS3 acts as a proinflammatory driver, promoting chemokine production via activation of MAPK pathways, transcriptional upregulation of EGR-1, and stabilization of mRNA through cytosolic translocation of HuR. Our findings reveal a dynamic interplay between RPL13A and RPS3, wherein RPL13A counteracts the proinflammatory effects of RPS3, offering a finely tuned regulatory axis in the inflammatory response to environmental toxins. These insights provide potential molecular targets for therapeutic intervention in toxin-induced inflammatory diseases of the gut, highlighting the non-canonical roles of ribosomal proteins in modulating immune responses to environmental stressors.